Effects of QDs exposure on the reproductive and embryonic developmental toxicity in mice at various pregnancy stages. Issue 4 (12th June 2020) - Chen, Ling; Zheng, Fengxia; Yang, Pengfei; Chen, Bolu; Aguilar, Zoraida P; Fu, Fen; Xu, Hengyi
Abstract: Quantum dots (QDs) have recently attracted considerable attention in the biomedical fields because of their unique and excellent optical properties. However, information on their health effects, particularly in the reproductive system, is limited. The present study focuses on the effects of intravenous injection of CdSe/ZnS QDs on the reproductive system and embryo development at various stages of pregnancy in mice. The CdSe/ZnS QDs intravenously injected in mice during pregnancy accumulated in the maternal liver, uterus and placenta. This accumulation affected the growth and development of the embryo during the early and middle stages of pregnancy. Moreover, genotoxicity to the placenta after exposure to CdSe/ZnS QDs was demonstrated by the increased expression levels of genes related to oxidative stress and apoptosis and the reduced expression levels of genes related to the nutrient and waste transportation. Alterations in the gene expression levels have hindered the transport of metabolites across the placenta, which in turn affected the ability of the fetus to obtain nutrients.